REGULATORY AND LEGAL REGULATION OF INFORMATION RELATIONS IN ENSURING THE BORDER SECURITY OF UKRAINE - Калюжний, Ростислав Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Review of the monograph by I.P. Kushnir «Regulatory regulation of information relations in the activities of the State Border Guard Service of Ukraine: theoretical and organizational aspects». The reviewed monograph provides a comprehensive analysis of regulatory and legal regulation of information relations in the activities of the State Border Guard Service of Ukraine, theoretical and organizational aspects, formulated sound recommendations for improving the effectiveness of information relations and areas of regulatory regulation. The reviewer concludes that the monograph is a significant contribution to solving complex methodological problems related to information relations. Theoretical-methodological and practical orientation of the study determine its relevance for the development of the information society, the circulation of information in the management of subordinate units of the State Border Guard Service of Ukraine, information and border security. Theoretical substantiations, conclusions and offers are of considerable interest both for legal science, and for practical activity of bodies and divisions of protection of the state border of Ukraine.